GENDER-JUST ANALYSIS OF QUR’ANIC VERSES ON WOMEN–MEN HOUSEHOLD RELATIONS: Analisa Adil Gender Terhadap Ayat-Ayat Tentang Relasi Perempuan dan Laki-Laki dalam Rumah Tangga - R. Muhammad Farhal Azkiya; Abdul Gofur; Eni Zulaiha (Senarai: Journal of Islamic Heritage and Civilization, 2026)
This research stems from the reality of marital relations that have not yet fully reflected the values of compassion and justice as taught in Islam, thereby necessitating a reassessment of the understanding of the roles and positions of each party within the family. The purpose of this study is to analyze Qur’anic verses on marital relations through a gender-just exegetical approach in order to attain an equitable and humane understanding. The method employed is qualitative, using a literature-based analysis of classical exegesis (Al-Ṭabarī, Al-Qurṭubī, Ibn Kaṯīr, and Az-Zamakhsyarī) as well as feminist exegesis (Nur Rofiah and Kiai Husein Muhammad). The findings indicate that patriarchal interpretations tend to position women as passive subjects, whereas feminist interpretations emphasize reciprocity, consent, and respect for women’s bodies. In conclusion, the Qur’an affirms that sexual relations constitute a spiritual and emotional interaction grounded in justice, compassion, and equality between husband and wife. The main scholarly contribution of this article lies in synthesizing classical and feminist exegesis to formulate a gender-just interpretive model of Qur’anic verses on marital relations within the framework of contemporary tafsir.